Effect of surface area on the wear properties of Al-based automotive alloy and the role of Si at eutectic level - Kaiser, Mohammad Salim; Hossain, Al-Kabir (Acta Polytechnica, 2024)
The efficiency of an engine material is closely correlated with its surface area. In order to investigate wear properties, effect of surface contact area as well as silicon addition at the eutectic level of Al-Cu-Mg alloy has been studied. This test is performed under room atmosphere and dry sliding conditions using a standard pin-on-disk apparatus. Weight reduction method is adopted to measure the wear rate in microns to get more accurate results. A load varying from of 5 to 50 N and a constant sliding speed of 0.77 ms−1 are maintained throughout the test. The test results show that a lower contact surface area has a negative impact on the wear properties having higher wear rate, while the coefficient of friction of the alloy and Si addition into the alloy improve the properties to some extent. Reduction of the contact surface area increases the unit pressure and decreased material volume causes softening of the alloy matrix, resulting in a higher wear rate and coefficient of friction. The Si addition offers such an improvement mostly for an increase in strength via the Si-rich intermetallic formation. A microstructural study confirms a lower abrasive wear with a minor plastic deformation on the worn surfaces of Si added alloy and wear with higher contact surface. The Si-added alloys contain the fine and strong Si-rich intermetallic, which are responsible for such a smooth worn surface.